BIM Application in Multi-Criteria Assessment of Suspended Brickwork Façade Production Methods for a Reconstructed Building - Viačeslav Zigmund; Jurgita Antucheviciene; Darius Migilinskas (Applied Sciences, 2023)
This research aims to promote a new cost-saving method for rebuilding old masonry brickwork façade by installing a suspended brickwork system. This research introduces a case study for rebuilding masonry façade by applying MCDM (multiple-criteria decision making) and BIM (building information modeling) methodologies with the evaluation of three types of brickwork façade installation alternatives prepared for production. The first type is the installation of suspended brickwork and mounting of brickwork lintels; the second type is the installation of suspended brickwork and pre-prefabricated stainless-steel components, which have been manufactured offsite, completed with adhesively bonded brick slips; and the third type is the installation of prefabricated suspended brickwork masonry panels. The main aim of the research is to promote a cost-saving production method by comparing these three alternative types of brickwork production using the BIM application in accordance with the multiple-criteria assessments. A multiple-criteria system was developed, and an expert survey was employed to estimate the relative weights of the criteria; afterwards, the alternatives were assessed using the WASPAS (Weighted Aggregated Sum Product Assessment) method. A BIM brickwork façade model was developed based on survey data, analyzed design solutions, and adaptation for the production of suspended brickwork elements. The final results and details regarding the best BIM applications in the multiple-criteria assessment of suspended brickwork façade are presented in the conclusions.